Understanding Nitrogen Transformations and Cycling for Sweet Corn Production in Sandy Soils - Rishi Prasad; George Hochmuth (EDIS)
Because sandy soils have low water and nutrient-holding capacities and Florida experiences high rainfall periodically, optimizing fertilizer use efficiency for sweet corn production is challenging. The preparation of nitrogen budgets and the implementation of effective management strategies can help farmers overcome these obstacles. This 4-page fact sheet discusses major concerns which call for nitrogen management in sweet corn production, nitrogen budget preparation and interpretation, and important differences between farm-gate and soil system budgets. Written by Rishi Prasad and George Hochmuth, and published by the UF Department of Soil and Water Science, May 2015.